(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article describes the theoretical and practical aspects of the composition of commodity material reserves, their recognition, organization and accounting in budget organizations. The practice of documenting the movement of goods and material reserves and reflecting them in the accounts has been researched. A scientific proposal and practical recommendations have been developed in relation to the improvement of the accounting of commodity material reserves in budget organizations.